(untitled) (Research, Society and Development, 2020)
Grain yield of bean (Phaseolus vulgaris L.) is affected by biotic and abiotic conditions, as well as by farmers’ management. In the Center-South region of Parana State, the successive cultivation of black bean cultivars is common. The objective of this study was to evaluate the growth and yield of six black bean cultivars after successive monocultivation. The experiment was conducted in the field with six black bean cultivars and four repetitions (blocks). The cultivar with the highest grain yield was BRS Esplendor, a cultivar with a high number of grains per area. IPR Tuiuiú had the second-best grain yield because of its high harvest index. The continuous monocultivation resulted in low grain yield because of the high incidence of Colletotrichum lindemuthianum. Although common, the practice of continuous monocultivation of black bean cultivars in the Center-South region of Parana results in low grain yield and should be avoided.